2017
DOI: 10.1108/mf-03-2016-0084
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical approach to financial distress prediction modeling

Abstract: Purpose The purpose of this paper is to examine a theoretical base for the financial distress prediction modeling over eight countries for a sample of 2,500 publicly listed non-financial firms for the period from 2000 to 2014. Design/methodology/approach The prediction model derived through the theory has the potential to produce prediction results that are generalizable over distinct industry and country samples. For this reason, the prediction model is on the earnings components, and it uses two different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 48 publications
(61 reference statements)
1
4
0
1
Order By: Relevance
“…Similarly, many recent researchers (Bapat & Nagale, 2014;Ciampi & Gordini, 2013;Kasgari, Salehnezhad, & Ebadi, 2013;S. Y. Kim, 2011;Mansouri et al, 2016;S.-S. Park & Hancer, 2012) and recently, Oz and Yelkenci (2017) concluded that ANN has dominance over LR in classifying companies to become bankrupt.…”
Section: Comparison Of Lr and Nnmentioning
confidence: 95%
See 1 more Smart Citation
“…Similarly, many recent researchers (Bapat & Nagale, 2014;Ciampi & Gordini, 2013;Kasgari, Salehnezhad, & Ebadi, 2013;S. Y. Kim, 2011;Mansouri et al, 2016;S.-S. Park & Hancer, 2012) and recently, Oz and Yelkenci (2017) concluded that ANN has dominance over LR in classifying companies to become bankrupt.…”
Section: Comparison Of Lr and Nnmentioning
confidence: 95%
“…This is because financial firm works under more diverse operating environment. Therefore, except from financial firms all industries sectors of non-financial firms are part of the population to introduce larger dataset and surely it will enhance the generalizability capacity of the estimating models (Oz & Yelkenci, 2017). The financial data of companies is computed from SBP-BSA 2010-2015.…”
Section: Sample Selectionmentioning
confidence: 99%
“…In addition, Ong et al [18], Alifiah [19], and Ahmad [20] defined a firm as financially distressed in terms of restructuring and arrangement, debt restructuring, and deteriorating financial conditions in accordance with the Malaysian laws. Oz and Yelkenci [21] employed negative stock return, restructuring, and low credit score classifications for identifying financial distress.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kondisi riil perusahaan diproksikan dengan Laba Sebelum Pajak. Financial distress untuk perusahaan dalam sampel penelitian didefinisikan memiliki laba sebelum pajak yang negatif selama dua tahun berturut-turut (Oz & Yelkenci, 2017). Pada penelitian Miswanto & Aslan (2019) menyatakan bahwa laba setelah pajak tidak mencerminkan kinerja keuangan yang sesungguhnya, dan disarankan menggunakan laba sebelum pajak yang mencerminkan kegiatan operasional perusahaan serta mencegah peluang adanya penghindaran pajak.…”
Section: Pembahasanunclassified